Rethinking Gerontology and Geriatrics in a Nepalese Context: A Scoping Review - Sharma, Tribhuwon; Aryal, Bhagwan; Malla, Nabina (Chaturbhujeshwar Academic Journal, 2025)
Nepal's elderly population constitutes 10.2% of the total, reflecting a rapid demographic transition, with projections estimating this will approach 14% by 2030. This scoping review systematically maps and examines gerontological and geriatric issues within Nepal by analyzing peer-reviewed literature and government reports published between 2000 and 2025. Six major thematic areas emerge: demographic transitions, policy inadequacies, rural-urban disparities, geriatric education, social security, and lessons from international models. Critical findings highlight limited access to specialist geriatric services (only 12% coverage), significant rural-urban differences, insufficient policy implementation, and minimal geriatric training in medical education (